Intertextuality as resource for building ELLs generic competence: a systemic functional linguistic view - Schulze, Joshua; Ramírez, J Andrés (Colombian Applied Linguistics Journal, 2007)
This research examines how elementary English language learners(ELLs) used intertextuality as a resource to compose informational texts. The research examines ELLs’ use of intertextuality (Fairclough, 1992, 2003; Lancia, 1997) as a resource for developing generic competence (Bhatia, 2002). Using the tools of critical discourse analysis (CDA) and systemic functional linguistics (SFL), the researchers locate instances of manifest intertextuality to evaluate the extent of reliance on intertextual resources. While findings suggest strong reliance on intertextual resources and thus the potential to see this appropriation as a form of “transgressive intertextuality” (Pennycook, 2004), the close SFL analysis revealed that students’ grammatical moves to make the text their own have the potential to increase their linguistic control over the target genre of informational text.